Anticoagulation Management and Outcomes in Patients With Covid-19 With Propensity Score Matching: A Multicenter Retrospective Cohort Study. (January 2022) - Kaur, Jasmeet; deLongpre, Jennifer; Koehler, Tracy; Laclair, Heather; Bowen, Monica; Khine, Justin; Khosrodad, Nadia; Jena, Nihar; Dixit, Priyadarshini; Yadav, Sumeet; Mogulla, Swathi M.; Coakley, Rob; et al.
Abstract : Background: Therapeutic doses of anticoagulation have been administered to patients with coronavirus-19 disease (Covid-19) without thromboembolism, although there is a lack of robust evidence supporting this practice. Study Question: To compare outcomes between patients admitted to the hospital for Covid-19 who received full-dose anticoagulation purely for the indication of Covid-19 and patients who received prophylactic doses of anticoagulation. Study Design: This is a multicenter retrospective cohort study, including 7 community hospitals in Michigan. Patients were >18 years of age, confirmed positive for Covid-19 by polymerase chain reaction, and admitted to the hospital between March 10 and May 3, 2020. Exposed group: Patients receiving therapeutic dose anticoagulation for Covid-19 for any duration excluding clinically evident venous thromboembolism, atrial fibrillation, and myocardial infarction; control group: Patients receiving prophylactic anticoagulation. Propensity score matching was used to adjust for the nonrandomized nature of the study. Measures and Outcomes: The primary endpoint: 30-day in-hospital mortality. Secondary endpoints: intubation, length of hospital stay, and readmissions in survivors. Results: A total of 115 exposed and 115 control patients were analyzed. Rates of 30-day in-hospital mortality were similar (exposed: 33.0% vs. control: 28.7%). Controlling for institution, there was no significant association between treatment and 30-day in-hospital mortality (hazard ratio: 0.63; 95% confidence interval: 0.37–1.06). Survivors had statistically similar length of hospital stay and readmission rates. Conclusions: We found no difference in mortality in patients with Covid-19 without clinically evident venous thromboembolism, atrial fibrillation, and myocardial infarction who received therapeutic versus prophylactic doses of anticoagulation. Abstract : Supplemental Digital Content is Available in the Text.